2021
DOI: 10.3389/fcell.2021.655552
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 Regulates the Development of Medullary Thymic Epithelial Cells and Contributes to the Establishment of Central Immune Tolerance

Abstract: Although some advances have been made in understanding the molecular regulation of mTEC development, the role of epigenetic regulators in the development and maturation of mTEC is poorly understood. Here, using the TEC-specific Sirt6 knockout mice, we found the deacetylase Sirtuin 6 (Sirt6) is essential for the development of functionally competent mTECs. First of all, TEC-specific Sirt6 deletion dramatically reduces the mTEC compartment, which is caused by reduced DNA replication and subsequent impaired proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 108 publications
(164 reference statements)
1
12
0
Order By: Relevance
“…Consistent with our previous reports 35 , the Foxn1-Cre mouse strain (a gift from Dr. Yu Zhang) 54 , 55 was crossed with Sirt6 loxp/loxp mouse strain (a gift from Dr. Zhenyu Ju) 56 , 57 to generate the Foxn1-Cre Sirt6 loxp/loxp mice and Foxn1-Cre negative littermate controls. Mice were maintained in the Institute of Zoology, Chinese Academy of Sciences (IOZ, CAS) specific pathogen-free conditions and approved by the Animal Ethics Committee of Institute of Zoology, Beijing, China.…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations
“…Consistent with our previous reports 35 , the Foxn1-Cre mouse strain (a gift from Dr. Yu Zhang) 54 , 55 was crossed with Sirt6 loxp/loxp mouse strain (a gift from Dr. Zhenyu Ju) 56 , 57 to generate the Foxn1-Cre Sirt6 loxp/loxp mice and Foxn1-Cre negative littermate controls. Mice were maintained in the Institute of Zoology, Chinese Academy of Sciences (IOZ, CAS) specific pathogen-free conditions and approved by the Animal Ethics Committee of Institute of Zoology, Beijing, China.…”
Section: Methodsmentioning
confidence: 86%
“…Previous studies have proven that SIRT6, as a key chromatin regulator, remodels chromatin by promoting chromatin relaxation, although it has diverse biological functions, such as genome stability, glucose metabolism, and tumor suppression, through multiple pathways 29 34 . We, therefore, bred Foxn1-Cre mice with Sirt6 flox/flox mice to obtain TEC-specific deletion of Sirt6 mice as reported recently 35 . TEC-specific Sirt6 deletion reduced the cell number of mTECs with an accelerated differentiation of CD80 - Aire - immature mTECs to CD80 + Aire - intermediate mature mTECs by promoting Spib expression 35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, H&E staining demonstrates more severe lymphocytic infiltration in multiple organs, including the kidney, lung, and liver. It is suggested that the establishment of central immune tolerance is disrupted after SIRT6 deletion [ 31 ]. Collectively, the expression of epigenetic regulator SIRT6 in TECs is responsible for the development and differentiation of the mTECs lines (Fig.…”
Section: The Development and Differentiation Of Tecs And Epigenetic Mechanismsmentioning
confidence: 99%